Utilization of High-Intensity Statins in Patients at Risk for Cardiovascular Events: A National Cross-Sectional Study. (January 2022) - Moorman, John M.; Boyle, Jaclyn; Bruno, Leah; Dugan, Sara; Everly, Lukas; Gustafson, Kyle; Hartzler, Caleb; Homan, Nathan; Joshi, Dankesh; King, Cynthia; King, Kevin; King, Philip K.; et al.
Abstract : Background: The 2013 American College of Cardiology/American Heart Association cholesterol guidelines, which identified four groups of patients at risk for atherosclerotic cardiovascular disease events, departed from the target-based approach to managing cholesterol. The impact of these guidelines on high-intensity statin use across the United States is unclear. Study Question: The primary objective was to evaluate the rate of high-intensity potential (HIP) statin use before and after the 2013 guidelines. The secondary objective was to identify predictors of HIP statin use within the study population. Study Design: A national cross-sectional study was conducted using data from the National Ambulatory Medical Care Survey. Office visits involving patients aged 21–75 years where criteria for HIP statin therapy were met were included. Visits involving pregnant patients were excluded. Measures and Outcomes: Prescribing trends of HIP statins were measured from National Ambulatory Medical Care Survey data before and after the 2013 guidelines. Multivariate logistic regression identified variables associated with prescribing HIP statins. Results: A total of 48, 884 visits were included, representing more than 940 million office visits nationally. HIP statins were listed in 9.5% and 16.5% of visits before and after 2013, respectively (odds ratio [OR] 1.88; 95% confidence interval [CI] 1.62–2.20). The strongest predictors of HIP statin use were antihypertensive use (OR 5.38, 95% CI 4.67–6.20), comorbid hyperlipidemia (OR 2.93, 95% CI 2.62–3.29), Black race (OR 0.63, 95% CI 0.49–0.81), and Hispanic ethnicity (OR 0.65, 95% CI 0.52–0.80). Conclusions: Prescribing rates for HIP statins increased after the release of the 2013 guidelines. The prescribing rates were lower than expected, especially in Black and Hispanic patients. These observations signify opportunities to improve the quality of care for patients who are at risk for atherosclerotic cardiovascular disease events in the United States.